Study of clinico-epidemiological profile of leprosy patients at tertiary care centre of South Gujarat region - Patel, Kautuk K.; Momin, Anjum M.; Mistry, Ankita A.; Vaishnani, Jignesh B. (International Journal of Research in Dermatology, 2020)
Background: Leprosy is a chronic feared illness causes by Mycobacterium leprae. It was eliminated as a public health problem in India in 2005. But still, India contributes more than 60% of all new cases of leprosy. Methods: A retrospective analysis of 307 patients attending the leprosy clinic of the dermatology out patient department, SMIMER, was done for a period of five years from January 2014 to December 2018. The data was analysed for clinical and epidemiological characteristics of the patients. Results: A total of 307 patients visited the leprosy clinic during the study period. More than half patients (60.3%) were between 21-40 years age group. There were 213 males and 94 females with male female ratio of 2.3:1. 72.3% (222) patients were suffering from multibacillary leprosy and 27.7% (85) had paucibacillary disease. Borderline tuberculoid leprosy was the most common type found in 83 patients (27.1%). 16 cases (5.2%) of childhood leprosy (less than 14 years of age) were noted. A total of 214 patients (69.7%) were migrants. Conclusions: Despite of decline at global and national level, leprosy cases show gradual increase. The high proportion of total cases, MB cases, and grade 2 disability cases are warning signs. Continued efforts are required to manage and prevent the disease.